MODERN EDUCATIONAL TECHNOLOGIES AS A CONDITION FOR THE SUCCESSFUL IMPLEMENTATION OF THE INDIVIDUAL EDUCATIONAL PROGRAM OF STUDENTS - Vasilyeva, Galina; Kalinina, Svetlana; Burenina, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the modern model of education the attention of teachers is paid to the implementation of the individual educational route of the student. The article discusses the possibilities of modern educational technologies. The problem field of research is a contradiction between the need for higher education to implement the individual educational route of the student and the lack of attention of teachers to the selection of appropriate educational technologies. The aim of the study was to study the possibilities of modern educational technologies to strengthen the individuality, subjectivity, human capital of the student.